2018
DOI: 10.1177/8755123318760970
|View full text |Cite
|
Sign up to set email alerts
|

Review of Literature: Pedagogical Content Knowledge and String Teacher Preparation

Abstract: In this literature review, we examine literature about pedagogical content knowledge (PCK) in relation to in-field and out-of-field teaching experience and pedagogical training in general education subjects, music subjects, and more specifically string music education. Out-of-field teaching has been defined as a lack of fit between teachers' preparation and their teaching assignments (Ingersoll, 1998). Our intention is to highlight the importance of providing non-string specialists who are assigned string clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 32 publications
1
20
0
2
Order By: Relevance
“…Although limited in time, the participants of the current study concluded that the ACL experiences they had in Introduction to Music Education and Elementary General Music Methods were an effective form of preparation for teaching elementary general music. ACL experiences have been discussed in research regarding preservice preparation as an approach to improve teaching (e.g., Brophy, 2002; Conway 2012; Groulx, 2016; Roulston et al, 2005), develop pedagogical content knowledge (Ballantyne, 2007; Grieser & Hendricks, 2018; Millican, 2008), and affect teaching efficacy (Prichard, 2017). Core teaching practices, as identified by researchers such as Millican and Forrester (2017), may also provide a framework within which music teacher educators can support the development of undergraduate students’ skills that will be used in music teaching regardless of specialization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although limited in time, the participants of the current study concluded that the ACL experiences they had in Introduction to Music Education and Elementary General Music Methods were an effective form of preparation for teaching elementary general music. ACL experiences have been discussed in research regarding preservice preparation as an approach to improve teaching (e.g., Brophy, 2002; Conway 2012; Groulx, 2016; Roulston et al, 2005), develop pedagogical content knowledge (Ballantyne, 2007; Grieser & Hendricks, 2018; Millican, 2008), and affect teaching efficacy (Prichard, 2017). Core teaching practices, as identified by researchers such as Millican and Forrester (2017), may also provide a framework within which music teacher educators can support the development of undergraduate students’ skills that will be used in music teaching regardless of specialization.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have discussed out-of-specialization teaching placements and preparation in various contexts (Grieser & Hendricks, 2018; Hamann & Ebie, 2009; Parker & Powell, 2014); however, elementary general music may be the most common class non–general music specialists teach (Groulx, 2016). A few researchers have explored why instrumentalists transition to elementary general music and how this has affected their teacher identity, providing a foundation for the current research (Corfield-Adams, 2012; Kuebel, 2017; Robinson, 2010; Shouldice, 2013).…”
mentioning
confidence: 99%
“…Así, el autor explica que existe una capacidad para adaptar aquello que los maestros entienden para sí mismos, en conceptos diseñados para el aprendizaje de los estudiantes, haciendo uso de metáforas, ejemplos demostrativos o nuevas formas de reorganización del saber (Shulman, 1987). El planteamiento inicial del CDC ha evolucionado hasta convertirse en una herramienta conceptual que sirve para comprender la manera en que funciona en la enseñanza y su proceso de desarrollo en diferentes disciplinas como las ciencias (Park & Oliver, 2008), las matemáticas (Ball et al, 2008) y la música (Grieser & Hendricks, 2018a;2018b;Millican, 2013Millican, , 2016Millican, , 2017Schiemann, 2017).…”
Section: Introductionunclassified
“…knowledge of mathematics; and pedagogical content knowledge (e.g. knowledge on how to teach mathematics) (Burroughs et al, 2019 [2]; Guerriero, 2017 [9]; Greenberg, Walsh and McKee, 2013 [11]). It is not entirely clear why general pedagogical knowledge has remained rather untargeted by research efforts, even though it has been widely acknowledged as an important prerequisite for successful teaching.…”
Section: Introductionmentioning
confidence: 99%